Proceedings of the Twelfth ACM International Conference on Web Search and Data Mining 2019
DOI: 10.1145/3289600.3290975
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Convolutional Generative Network for Next Item Recommendation

Abstract: Convolutional Neural Networks (CNNs) have been recently introduced in the domain of session-based next item recommendation. An ordered collection of past items the user has interacted with in a session (or sequence) are embedded into a 2-dimensional latent matrix, and treated as an image. The convolution and pooling operations are then applied to the mapped item embeddings. In this paper, we first examine the typical session-based CNN recommender and show that both the generative model and network architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
340
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 440 publications
(355 citation statements)
references
References 31 publications
5
340
0
Order By: Relevance
“…In the next sections, we will further summarize and evaluate the factors that might impact the performance of a DL-based model, which is expected to better guide future research. [41], [42] TB RNN [8], [43], [44], [51]- [56] [13], [45]- [50], [57], [58] CNN [24], [25], [60], [61] MLP [69], [71] att.…”
Section: Discussionmentioning
confidence: 99%
“…In the next sections, we will further summarize and evaluate the factors that might impact the performance of a DL-based model, which is expected to better guide future research. [41], [42] TB RNN [8], [43], [44], [51]- [56] [13], [45]- [50], [57], [58] CNN [24], [25], [60], [61] MLP [69], [71] att.…”
Section: Discussionmentioning
confidence: 99%
“…However, the above RNNs-based methods depend on a hidden state of the entire past that cannot effectively utilize parallel computing within a check-in sequence. This also results in a speed limit on the model's training and evaluation process [22].…”
Section: Deep Learning-based Poi Recommendation Methodsmentioning
confidence: 99%
“…It abandoned RNN structures and demonstrated that this CNN-based recommender can achieve superior performance to the popular RNN model in the Top-N sequential recommendation task. Yuan et al [22] proposed a simple, efficient, and highly effective convolutional generative network for next-item recommendation, which was capable of learning high-level representation from both short-and long-range item dependencies. However, the above two sequence recommendation methods do not consider the spatiotemporal contextual information, and they are not specialized solutions to POI recommendations.…”
Section: Deep Learning-based Poi Recommendation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we expect this encoder to capture the purchasing pattern iPhone → iPhone case → iPhone charger if it appears frequently in user sequences. As a result, we believe the Recurrent Neural Network (RNN [36]) and the Temporal Convolutional Network ( [3,53,59]) are fitting potential architectural choices. Such neural architectures have shown superb performances when modeling high-order causalities.…”
Section: Three Different Range Encodersmentioning
confidence: 99%